Scientific Learning to Improve Critical Thinking Ability - IIK NURHIKMAYATI; MOHAMAD GILAR JATISUNDA (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
The importance of the ability to think critically in mathematics learning is contrary to the fact that the development of these abilities is still not optimal. Not many teachers creatively develop critical thinking skills during the learning process. The consequence of the implementation of the 2013 curriculum is the use of a scientific approach to learning, including mathematics. Steps in scientific learning include: (1) observing; (2) ask; (3) collecting information; (4) associate; and (5) communicating. These five steps provide great opportunities for students to be able to develop mathematical critical thinking skills. This study describes the implementation of a scientific approach in learning mathematics, especially in improving mathematical critical thinking skills.